Negócios Sociais em Foco: O caso da Yunus Social Business - Lilian de Lima Pires (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
In a global context marked by instability and crisis, the exclusively economicist approach of organizations is questioned, since profit-driven companies end up contributing to the aggravation of concentration of power and wealth and to the deepening of inequalities, poverty and Ambiental degradation. When considering the relevance of the role of organizations in contemporary society, the importance of understanding organizational models capable of contributing to the mitigation of current social problems emerges. The focus of this article are ventures whose main purpose is to solve a social problem using business methods. Thus, this article aims to describe the social business accelerator Yunus Social Business (YSB) and its way of acting in the global context. We chose a qualitative exploratory and descriptive approach with the use of documentary analysis. The ways in which these ventures are described, their areas of action and some results achieved are described. The relevance of the YSB is recognized, however, it is problematic if the social business operations follow a palliative logic, contributing locally to the mitigation of social problems without changing the same structures causing such crises.